Determining the net financial risk for decision making in business interactions - Hussain, Omar; Dillon, Tharam S.; Chang, Elizabeth; Hussain, Farookh (IEEE Computer Society, 2009)
In a business interaction, risk highlights and expresses the uncertainty associated with the achievement of desired outcomes. Failure to achieve these outcomes will result in the interacting userexperiencing financial loss in the business interaction. The level of financial loss that could be experienced plays a very important role on the user while forming a business interaction. Further, by ascertaining the financial loss the user can take steps by which it can manage the level of risk. The level of financial loss that could be experienced depends upon the different types of uncertain outcomes associated in the interaction. In this paper we will propose a methodology by which the user in a digital business ecosystem interaction can capture the different types of uncertainties and ascertain the financial risk that could be experienced from it.